2012
DOI: 10.1097/mao.0b013e318254501b
|View full text |Cite
|
Sign up to set email alerts
|

Dexamethasone Levels and Base-to-Apex Concentration Gradients in the Scala Tympani Perilymph After Intracochlear Delivery in the Guinea Pig

Abstract: Hypothesis To determine whether intracochlearly applied dexamethasone will lead to better control of drug levels, higher peak concentrations and lower base-to apex concentration gradients in scala tympani (ST) of the guinea pig than after intratympanic (round window, RW) application. Background Local application of drugs to the RW results in substantial variation of intracochlear drug levels and significant base-to apex concentration gradients in ST. Methods Two μL of dexamethasone-phosphate (10 mg/mL) wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
42
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 55 publications
(42 citation statements)
references
References 34 publications
0
42
0
Order By: Relevance
“…The distinction of the different audiometric curves, rarely employed in the literature [Battaglia et al, 2008;Filipo et al, 2010;Plontke et al, 2009], is particularly useful in the predictive determination of the effectiveness of the steroid therapy. This greater efficacy in down-sloping curves, observed analyzing the hearing outcome according to the two criteria, may be attributed to the higher concentration of the drug in the basal turn of the cochlea [Hahn et al, 2012], whilst it is still unclear as to why up-sloping curves present better results with local therapy compared to systemic therapy.…”
Section: Discussionmentioning
confidence: 92%
“…The distinction of the different audiometric curves, rarely employed in the literature [Battaglia et al, 2008;Filipo et al, 2010;Plontke et al, 2009], is particularly useful in the predictive determination of the effectiveness of the steroid therapy. This greater efficacy in down-sloping curves, observed analyzing the hearing outcome according to the two criteria, may be attributed to the higher concentration of the drug in the basal turn of the cochlea [Hahn et al, 2012], whilst it is still unclear as to why up-sloping curves present better results with local therapy compared to systemic therapy.…”
Section: Discussionmentioning
confidence: 92%
“…Perilymph drug levels appear to become less variable when drug is delivered for more prolonged periods [Wang et al, 2009]. However, concentration levels in the basal part of scala tympani (ST) typically reach less than 3% of the applied concentration (summarized in [Hahn et al, 2012]). More consistent and efficient delivery would be expected when the solution was directly injected into perilymph.…”
Section: Introductionmentioning
confidence: 99%
“…More consistent and efficient delivery would be expected when the solution was directly injected into perilymph. With applications by intracochlear injection into the cochlear apex [Salt et al 2006] or by injections through the RW membrane [Salt et al 2007, Hahn et al 2012], concentrations in perilymph were found to be higher, with lower variation and the substances were distributed more uniformly along scala tympani. Effective deliveries of viral vectors have been accomplished with single intracochlear injection procedures [Stover et al 1999; Kawamoto et al, 2001; Staecker et al, 2014].…”
Section: Introductionmentioning
confidence: 99%
“…There have been numerous pharmacokinetic studies of locally-applied corticosteroids in animals (Nomura 1984;Parnes et al 1999;Chandrasekhar et al 2000;Bachmann et al 2001;Hahn et al 2006Hahn et al , 2012Liu et al 2006;Plontke et al 2008b;Yang et al 2008;Wang et al 2009;Borden et al 2011;Salt et al 2011a) and humans (Bird et al 2007;Bird et al 2011), but only a subset of these studies has been analyzed quantitatively to derive an elimination rate. Plontke and analyzed prednisoline data of Bachmann et al (2001) from guinea pigs and found it to be consistent with an elimination half-time from perilymph of 130 min.…”
Section: Introductionmentioning
confidence: 99%